The Influence of Risk Factors on Project Cost in The Sigli-Banda Aceh Toll Road Project - Mariama Badjie (Return : Study of Management, Economic and Bussines, 2024)
Effective management of risk is critical to the success of any construction project. The importance of risk management has grown as projects have become more complex. This study examines the influence of risk factors on project cost in the Sigli-Banda Aceh toll road project. It identifies 47 common risk indicators and categorises them into six risk factors, emphasize the need for improved risk management strategies in complex construction projects. The research question of this study is to know the influence and relationship of risk factors on project cost in the Sigli-Banda Aceh toll road project. The purpose of this study is to determine the risk factors that influence and relate to project cost in the Sigli-Banda Aceh toll road project. The data was analysed with statistical tools to determine the rank of factors affecting project costs. The research method used quantitative, using hard data on Likert scale, and qualitative, using the opinions of the respondents, with primary sources and secondary data. This research involved the project director, site supervisors, engineers, safety environment officer, and finance manager from PT Hutama Karya. Data collection techniques include the distribution of questionnaires. The data analysis technique uses correlation and multiple linear regression analysis methods with the help of SPSS software. According to the result analysis, all the factors have a moderate relationship with the project cost, and there are four factors that have a significant relationship with the project cost, namely material risk, equipment risk, construction method risk, contractor managerial risk, and construction safety risk.